Current advancements in microneedle technology for therapeutic and biomedical applications - Olivia Sen; Poulami Poddar; Poulami Sarkar; Sanchita Das; Sreejan Manna (Sensors International)
Microneedle technology has gained large interest as an innovative biomedical device to deliver molecules to the targeted site through the skin layers. Microneedle consists of microscale needle with a specific length about 0.1–1 mm. In comparison to conventional transdermal delivery approaches, the microneedle technique has several advantagesincluding minimal invasiveness, painlessand convenient administration, with higher patient compliance. Microneedles are categorized into several types such as solid microneedle, coated microneedle, hollow microneedle, dissolvable microneedle, hydrogel microneedle, swellable microneedle, and porous microneedle. Microneedles can be made of different materials, and may vary in size and forms. They may also vary in design depending on composition, manufacturing process and area of application. Silicon, stainless steel, polymers, coating materials, biodegradable materials, several crosslinking techniques and biosensing devices are used to fabricate microneedles. can be employed as a leading novel technology for drug administration, vaccinations, cosmetics, diagnostics, tissue engineering, cancer studies, and wound care. This review narrates the fabrication techniques of microneedles alongside its applications in drug delivery and biomedical field including sensory applications.